Ventricular Septal Defect And Maternal History Of Epilepsy: A Case Report - Ngurah Agung Reza Satria Nugraha Putra; Nyoman Suciawan; Ida Bagus Komang Arjawa (Faculty of Medicine, Universitas Jember, 2024)
Pregnancy with epilepsy can cause major risks for both the mother and the offspring. It is known that the use of antiepileptic drugs (AEDs) during pregnancy can increase the risk of cardiac malformations. This journal reports a 19-day-old male infant who came with complaints of shortness of breath and a blue lip 2 days before admission. The mother had a history of epilepsy and had regularly taken epilepsy medication since before pregnancy. Physical examination revealed cyanotic lips, chest wall retraction, coarse crackles, and murmurs. The patient's symptoms and signs were associated with congenital heart disease, so he was further observed in the NICU. After bedside echocardiography, the results showed a patent foramen ovale and perimembranous ventricular septal defect. The teratogenic effect of AED is thought to be one of the major causative factors of congenital heart disease. A ventricular septal defect is the most common cardiac malformation found in population-based studies. The long-term effects of AED exposure during pregnancy require further investigation, both in terms of the type of AED (old or new) and the duration of AED consumption. It is important to educate mothers-to-be about this, especially to avoid the risk of congenital heart disease in their offspring. Keywords: epilepsy, ventricular septal defect, cardiac malformation.